The Effect of Teamwork and Trust on Job Satisfaction of The Teachers of The State High School in Bekasi City - Suparno Suparno; Sutjipto Sutjipto; Suryadi Suryadi (International Journal of Education, Information Technology, and Others, 2020)
The objective of this research was to determine the effect of teamwork, and trust toward Job Satisfaction of the teachers high school in Bekasi City. This research was quantitative approach and path analysis method was applied to analyse the data. In this research, the target population size of this research is 889 teachers of state high school and research samples has been choosen as a unit analysis as much as 276 teachers of state high school in Bekasi City. The results of the research that: (1) teamwork has a direct positive effect on Job Satisfaction; (2) trust has a direct positive effect on profesional commitment; The research suggested that teamwork, and trust were important determinants of teacher’s Job Satisfaction.